2023
DOI: 10.1021/acs.langmuir.3c02672
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying-Assisted ZIF-67 Template-Derived Co@NCS Porous Composite as Sulfur Cathode Host for Improved Li–S Battery Performance: Deconvolution of Diffusive and Capacitive Li+ Storage

Suresh Archana,
Perumal Elumalai

Abstract: A zeolitic imidazole framework (ZIF-67) templatederived cobalt@nitrogen-doped carbon−sulfur composite (ZIF-Co@ NCS) was synthesized using a freeze-drying method and explored for lithium−sulfur (Li−S) batteries. Material characterizations confirmed the formation of the ZIF-Co@NCS composite. To fabricate the Li−S battery in a coin-type CR-2032 cell, the as-synthesized ZIF-Co@NCS composite having a sulfur content of ∼65% was used as a cathode material and coupled with a lithium metal anode. This battery demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…They can be fitted to the equivalent circuit shown in the inset of Figure S8. It is observed that the shunt resistance ( R s ) and charge transfer resistance ( R ct ) values increased after conducting the cycle life analysis, implying a bit degradation of the electrode and electrolyte, as generally reported in the literature . The low R ct value observed indicates the smooth charge transfer reaction facilitated by the sea-urchin like NiO-CoO heterostructure electrode.…”
Section: Results and Discussionsupporting
confidence: 65%
“…They can be fitted to the equivalent circuit shown in the inset of Figure S8. It is observed that the shunt resistance ( R s ) and charge transfer resistance ( R ct ) values increased after conducting the cycle life analysis, implying a bit degradation of the electrode and electrolyte, as generally reported in the literature . The low R ct value observed indicates the smooth charge transfer reaction facilitated by the sea-urchin like NiO-CoO heterostructure electrode.…”
Section: Results and Discussionsupporting
confidence: 65%